Experimental and numerical investigation on compressive strength and crack behavior of rock-like specimens with open flaws under confining loads - Sun, Shaorui; Wang, Jin; Le, Huilin; Fan, Haotian; Wang, Wuchao (Frontiers in Earth Science, 2022)
The engineering problems are related to the failure of geological material, especially that of jointed rock masses. To investigate the influence of confining stress and inclination angle β on cracking behavior and failure mechanism, triaxial compression tests are conducted on rock-like samples containing parallel opening flaws. There are two patterns: tensile failure and tensile-shear failure, and each occurrence has an equal frequency. Nine crack modes are summarized, and the most special one is mode 8 which is mainly observed in samples with β=60° at high confining pressure. Both the compressive strength and internal friction in samples with β=60° are the smallest in the experiments, and those in samples with β=65.31° based on the improved theory the are smallest. The compressive strength decreases with the increase of inclination angle β when 0°≤β≤60°, however, it increases as inclination angle β increases when 60°<β≤90°. This phenomenon is found in laboratory experiment and numerical tests, and is almost even in accordance with theoretical results. Numerical compression tests are performed to investigate the influence of the width-to-length ratio of opening flaw on compressive strength, and to make verification of the improved theory reliability. Compared numerical results with the two kinds of theoretical results, the width-to-length ratio has an obvious impact on compressive strength and the opening fracture intensity factor KⅠ.